PENGARUH FRAKSI AIR EKSTRAK BAWANG PUTIH TERHADAP KADAR KALIUM IODAT DALAM GARAM BERIODIUM - Komari Komari; Dian Sundari (Persagi, 2009)
ABSTRACT Background: Interference problems due to iodine deficiency (GAKY) in Indonesia due to poor environmental iodine substance. One of the government's efforts to overcome this is GAKY beriodin fortification of salt with iodine added salt form of potassium iodat (KIO3). From several studies were conducted in the salt iodine content can be lost or reduced during storage, transport or during food processing. Garlic is the spice is often used in cooking. The use of garlic as a spice in cooking can affect potassium iodat damage. Methods: The study was conducted to determine the fraction of the homogenate and the garlic extract with dichloromethane solvent can reduce levels of potassium iodine in table salt beriodin. Research using the method of analysis iodometri and high performance liquid chromatography (HPLC) with isokratik binary solvent methanol: water (1:1) in different flow rates of 1.6, 1.5, 0.75 and 0.5 ml / min to separate fraction of garlic extract. Results: The results showed that the three times repeated, homogenate can reduce levels of potassium iodat for 23, 20 and 20%. Percentage decrease in potassium iodat from the water fraction of 23, 25 and 26%, while the homogenate can lower potassium iodat of 18, 17 and 19%. For HPLC analysis, the flow rate 1.6 ml / min obtained three components with retention time of 1.685; 1.788 and 2.218 min. Separation of the flow rate 1.5 ml / min sample dihasikan two components, namely the retention time of 1.875 and 2.417 min. Separation of flow rate 0.75 ml / min is the best separation of the sample into four components with retention times 3.647; 3.837; 4.113 and 4.845 min, the peaks are detected at the retention time of less than 1.5 minutes and more than 6 minutes. At the flow rate 0.5 ml / min, samples were separated into three components at the retention time of 2.63; 2.927 and 4.382 min. Garlic, both homogenate and the fraction of water can reduce levels of potassium salt iodat in beriodin. [Penel Gizi Makan 2009, 32(2): 148-155] Key words: fortified salt, potassium iodine, garlic, extracts